Immunological changes in patients with chronic heart failure - Olga Malgazdarova; Bulat Kupenov; Akmaral Moldazhanova; Zhanat Bekzhigitova (National Scientific Medical Center, 2018)
Chronic heart failure - symptom complex arising in the outcome of cardiovascular diseases of various etiologies. At the moment heart failure is widespread and has become a pandemic. This fact led to the need to clarify the known mechanisms of pathogenesis and the search for new ways of diagnostics therapy and ultimately to improve methods of monitoring the course of heart failure. The wide diagnostic possibilities of modern medicine did not give a clear understanding of the mechanisms of involvement of the immune system links in the pathogenesis of chronic heart failure. It remains an open question, concluded in the "cytokine theory" of the pathogenesis of chronic heart failure, about the cause-and-effect relationship of the immune response and heart failure.